2022
DOI: 10.3390/polym14245412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Strength of the Interface for Abaca Fiber Reinforced Hdpe and Biope Composite Materials, and Its Influence over Tensile Properties

Abstract: In this study, tensile properties of abaca-reinforced HDPE and BioPE composites have been researched. The strength of the interface between the matrix and the reinforcement of a composite material noticeably impacts its mechanical properties. Thus, the strength of the interface between the reinforcements and the matrices has been studied using micromechanics models. Natural fibers are hydrophilic and the matrices are hydrophobic, resulting in weak interfaces. In the study, a coupling agent based on polyethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…The addition of MAPE did not significantly improve the modulus of the composite, which contradicts the findings in many literature sources [ 38 , 61 , 64 ]. Surprisingly, the composite exhibited a slightly lower modulus than its counterpart without MAPE.…”
Section: Discussion and Application Example Of Rhdpe Compositecontrasting
confidence: 90%
See 3 more Smart Citations
“…The addition of MAPE did not significantly improve the modulus of the composite, which contradicts the findings in many literature sources [ 38 , 61 , 64 ]. Surprisingly, the composite exhibited a slightly lower modulus than its counterpart without MAPE.…”
Section: Discussion and Application Example Of Rhdpe Compositecontrasting
confidence: 90%
“…Apparent moduli for PALF and NFM were calculated by linear curve fitting and the value extrapolated to reinforcement volume fraction of unity to 10.82 and 5.47 GPa, respectively. The apparent modulus for PALF obtained here is slightly less than 11.70 for Abaca fiber in rHDPE system containing MAPE at 8 wt.% [ 61 ]. However, it should be noted that the rHDPE/Abaca fiber samples were prepared by injection molding, in which there could be significant contribution from matrix orientation.…”
Section: Discussion and Application Example Of Rhdpe Compositementioning
confidence: 97%
See 2 more Smart Citations
“…Previous research has focused on the use of Musa Textilis (abaca) as reinforcement in HDPE and BioPE composite materials, evaluating the tensile strength, tensile stiffness, and micromechanical characteristics of the composites [ 26 , 27 ]. These studies confirmed that, as expected, these materials exhibit superior mechanical properties compared to the matrix [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%